2006
DOI: 10.1038/sj.jcbfm.9600186
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Oxygen Extraction in the Visual Cortex during Activation in Mild Hypoxic Hypoxia Revealed by Quantitative Functional Magnetic Resonance Imaging

Abstract: Functional magnetic resonance imaging (fMRI) techniques were used to study haemodynamic and metabolic responses in human visual cortex during varying arterial blood oxygen saturation levels (Y sat , determined by pulse-oximeter) and stimulation with contrast-reversing checkerboards. The visual-evoked potential amplitude remained constant at lowered Y sat of 0.8270.03. Similarly, fMRI cerebral blood flow (CBF) responses were unchanged during reduced Y sat . In contrast, visual cortex volume displaying blood oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 44 publications
7
30
0
Order By: Relevance
“…The detection of lactate is challenging due to its low concentration and limited chemical shift resolution of the 1 H spectrum. The increase in lactate sensitivity gained from higher field strength (3T), edited MRS and the lactate-specific analysis as applied here and previously (6) represents a development from other studies (13) that have not detected changes in lactate during a hypoxic challenge.…”
Section: Discussionmentioning
confidence: 76%
“…The detection of lactate is challenging due to its low concentration and limited chemical shift resolution of the 1 H spectrum. The increase in lactate sensitivity gained from higher field strength (3T), edited MRS and the lactate-specific analysis as applied here and previously (6) represents a development from other studies (13) that have not detected changes in lactate during a hypoxic challenge.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, an increase in brain activity also leads to increased neurotransmitter cycling rates (24,29), which may ultimately change the concentrations of neurotransmitters such as glutamate/glutamine and γ-aminobutyric acid (28,30,31). For instance, the transient increases in the concentrations of lactate and glutamate, accompanied with the tendency of concentration decrease in Glc, have been observed in the human visual cortex during sustained visual stimulation (19,27,28,32,33). It was also reported that there are significant changes in a number of brain metabolites and neurotransmitters, including the ratio of PCr versus Cr, γ-aminobutyric acid, glutamine, and glutamate, as well as neurotransmission cycling rate at near-freezing body temperature in hibernating mammals (31).…”
Section: Discussionmentioning
confidence: 99%
“…Vafaee and Gjedde, 2000; Lu et al, 2004; Vafaee and Gjedde, 2004; Tuunanen and Kauppinen, 2006; Tuunanen et al, 2006; Chiarelli et al, 2007a,b; Ances et al, 2008; but, see Leenders et al, 1990). Mechanisms posited to mediate these differences include variation in oxygen metabolic requirements across cortex (Tuunanen et al, 2006), oxygen delivery, or blood flow alterations under certain conditions or in certain cortical areas (Vafaee and Gjedde, 2000; Lu et al, 2004), variable neurometabolic-flow coupling (Vafaee and Gjedde, 2004), and the accurate estimation of M (an index of maximal BOLD responding; Chiarelli et al, 2007a). Regardless of the precise mechanism behind this variability, the end result is that the BOLD response can be difficult to interpret across healthy, young cortex, and it can be even more complicated to interpret when making comparisons between younger and older groups (cf.…”
Section: Introductionmentioning
confidence: 99%